Simulation of latent-heat thermal storage integrated with room structures - Charvat, Pavel (Materiali in tehnologije, 2012)
The phase change of a material is accompanied by a release or absorption of a considerable amount of heat. That makes a phase change a phenomenon effectively usable in various thermal storage applications. There are many materials with a melting temperature lying within the thermal comfort range for indoor environments. These materials can be utilized in building-integrated thermal storage. The performance of such latent-heat thermal storage integrated with the room structures was investigated through numerical simulations and experiments. The studied case involved two adjacent rooms of the same dimensions. The hydrated-salt-based phase-change material (PCM) was used as a thermal storage medium. A comparative approach was adopted in which the internal structures of one of the rooms contained the PCM, while the structures in the other room did not. The simulation model of the rooms was created in the numerical simulation tool TRNSYS 17, and this model was coupled with a PCM model created in MATLAB. The enthalpy method was used for the simulation of the phase change. This approach allowed for different time steps in the room model and the PCM model (the time step in the PCM model needed to be much shorter). The data from the real-scale experiments (ventilation rates, temperature of supply air, outdoor temperature, solar radiation intensity, etc.) as well as the physical properties of the PCM acquired in the laboratory testing were used as inputs to the simulation models. The analysis of the results was carried out, in which the simulation results were compared with the experimentally obtained data.
Keywords: latent-heat storage; latentna toplota; hranjenje toplote; phase change; fazni prehodi; model; modeli